Comparing outcome of patients with coronary artery disease and dilated cardiomyopathy in ICD and CRT recipients: data from the German DEVICE-registry - Wasmer, Kristina; Köbe, Julia; Andresen, Dietrich; Zahn, Ralf; Spitzer, Stefan G.; Jehle, Joachim; Brachmann, Johannes; Stellbrink, Christoph; Martens, Eimo; Hochadel, Matthias; Senges, Jochen; Klein, Helmut; et al. (Clinical research in cardiology, 2013)
The purpose of this study was to evaluate whether there are differences in use and outcome of implantable cardioverter defibrillator (ICD) therapy with or without cardiac resynchronization therapy (CRT) between patients with underlying coronary artery disease (CAD) and non-ischemic dilated cardiomyopathy (DCM).